Effect of delivery hospital busyness on early mortality in small preterm infants: a Finnish population-based cohort study in 2006–2016 - Mika Gissler; Sari Räisänen; Seppo Heinonen; Sture Andersson; Riitta Vilkko; Markus Leskinen (BMJ Open)
Objectives To evaluate the effect of delivery hospital busyness on the postnatal condition and the perinatal mortality among small preterm infants born at ≤32+0 gestational weeks.Design The daily delivery volume distribution is defined as lowest 10% (‘quiet’) and highest 10% (‘busy’) delivery-volume days, and days between (80%) as optimal delivery-volume days. We analysed differences in the incidence of selected adverse outcomes between quiet and busy days compared with optimal delivery-volume days by logistic regression followed by crude (ORs) and adjusted ORs (aORs) with 99% CIs.Setting A population-based cohort study based on prospectively collected real-world data from five university hospitals and 21 non-tertiary-level delivery hospitals in Finland, 2006‒2016.Participants 4323 small preterm infants.Primary outcome measures Umbilical cord pH ≤7.05, Apgar score 0–3 points at the age of 1 min, Apgar score 0–3 points at age 5 min, birth asphyxia (International Classification of Diseases-10 code), resuscitation with intubation.Secondary outcome measures Perinatal mortality comprising stillbirths and early neonatal deaths (<7 days).Results Busy days (busy vs optimal) showed no correlation with the primary birth-related outcomes. However, in the university hospitals, quiet days were associated with 80% lower odds of asphyxia (aOR 0.20, 99% CI 0.08 to 0.48) and 47% lower odds of resuscitation (aOR 0.53, 99% CI 0.39 to 0.72) compared with their incidence on optimal days.In university hospitals, the odds of early neonatal mortality among small preterm infants on busy days were twofold (aOR 2.08, 99% CI 1.26 to 3.45) than on optimal days. In the non-tertiary hospitals, however, this difference was statistically non-significant (aOR 0.68, 99% CI 0.19 to 2.45).Conclusions In the tertiary university delivery hospitals, busyness was associated with a twofold increase in early neonatal mortality among small preterm infants, whereas infants’ condition at birth on busy days was comparable to their condition on optimal days. Neonatal capacity in tertiary units during busy days may be critical under stress.